Peningkatan Daya Saing Usaha Mikro Kecil Melalui Pelatihan Pemasaran Digital - Mubarak, Abdullah; Apriliani, Lili; Aidil Fitri, Anugrah; Sam, Marwah Amaliah Putri; Hidayatullah, Syarif (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Micro and Small Enterprises (MSEs) in Desa Kassi face challenges in digital marketing due to their reliance on conventional methods, such as direct sales from home, which limit their market reach and product competitiveness. The Capacity Building Program for Student Organizations (PPK Ormawa) by MP Ekolibrium FEB UNM was designed to address these issues through training that includes business social media management, the use of websites and e-commerce platforms, and the creation of engaging and interactive digital content. The methods implemented include face-to-face training, door-to-door mentoring, and ongoing evaluations. As a result, MSEs are now capable of managing business social media, leveraging websites and e-commerce platforms, and producing creative content that enhances product appeal. A significant outcome of this program is the establishment of the UMK Center, serving as a marketing hub through websites and marketplaces. This program not only improves digital marketing skills but also expands market reach and enhances the competitiveness of MSEs in Desa Kassi.